Mesoscale Cyclonic Vortices Embedded in the South Atlantic Convergence Zone Associated with Natural Disasters in the State of São Paulo, Brazil - Silva, Joao Pedro Rodrigues; Ynoue, Rita Yuri (Anuário do Instituto de Geociências, 2023)
Natural disasters (NDs) have been observed more frequently and with increasing intensities in Brazil. The South Atlantic Convergence Zone (SACZ) is identified as one of the main meteorological systems responsible for the NDs, however, intense rainfall does not occur along its entire length but is restricted to some locations within the band of cloudiness that defines it. Thus, the objective of this study is to analyze occurrences of mesoscale cyclonic vortices (MCV) in SACZ events that were associated with NDs in the state of São Paulo from 2013 to 2017 using data from the ERA5 Reanalysis, as well as to analyze one case study. To account for SACZ events, surface synoptic charts, observed and estimated precipitation data were used. ND events were selected from the Integrated Disaster Information System (S2ID) database. The methodology used by Quadro (2012) was adapted to identify MCV. The results showed 62 SACZ events, of which 28 were associated with NDs, and, of these, 10 presented MCV. The MCVs were separated into two groups: 1) MCVs in the SACZ events that showed precipitation at the location of the MCV and NDs and 2) MCVs in the SACZ events that did not show precipitation at the location of the MCV and NDs. Group 1 events were characterized by convergence at low levels and divergence at high levels of the atmosphere, vorticity values lower than -8 x 10-4 s-1 predominating at low levels (850–900 hPa), demonstrating a relationship with the highest precipitation accumulations and possibly with the occurrence of NDs. In the events of group 2, there was a predominance of negative values of vorticity in medium and high levels, the lack of a pattern in the field of divergence in the atmospheric levels, as well as lower values in the accumulated precipitation compared to the events of group 1. The case study was from January 11 to 15, 2016, associated with NDs in 8 cities. As a result, it was obtained that MCV was coupled in the atmosphere and the precipitation associated with it represented more than 37% of all the precipitation of the SACZ event, making it possible to attribute to the MCV a contribution in the occurrence of NDs caused by precipitation.